Answer:
Step-by-step explanation:
Easy 54320
Answer:
see below
Step-by-step explanation:
(ab)^n=a^n * b^n
We need to show that it is true for n=1
assuming that it is true for n = k;
(ab)^n=a^n * b^n
( ab) ^1 = a^1 * b^1
ab = a * b
ab = ab
Then we need to show that it is true for n = ( k+1)
or (ab)^(k+1)=a^( k+1) * b^( k+1)
Starting with
(ab)^k=a^k * b^k given
Multiply each side by ab
ab * (ab)^k= ab *a^k * b^k
( ab) ^ ( k+1) = a^ ( k+1) b^ (k+1)
Therefore, the rule is true for every natural number n
What’s this?
Btw thanks for the points
Your answer is right. to solve it you would move the 10 over to get 10x^2-29x+10=0. i would solve by chunking and breaking -29x into -25x and -4x. This will give us (10x^2-25x)+(-4x+10). now factor both get inside the parenthesis the same. 5x(2x-5)+-2(2x-5). Now combine the factors you took out with what is inside to get (5x-2)(2x-5)
It equals 80000
I got that by doing basic math
(4x10)= 40
(2x10^3)= (2x1000)= 2000
(40)(2000)=80000
Hope this helps you a lot!!! :)